ANALISA YURIDIS PENGAWASAN MANAJERIAL PEKERJA OUTSOURCING SETELAH BERLAKU UNDANG-UNDANG CIPTA KERJA - Taufika Hidayati; Lendra Faqrurrowzi; Yulia Tiara Tanjung (Universitas Labuhanbatu, 2022)
In the business world, outsourcing is one of the strategies in providing services or materials to help the company's performance to stay focused on the main activities. Article 64 of Law Number 13 of 2003 concerning employment states that not all types of work can use outsourcing, including activities that are core to the company. After the enactment of Law Number 11 of 2020 concerning Job Creation, it removed this limitation which of course affected the quality and privacy of the company. In this study, the author will examine managerial supervision related to the quality of outsourcing workers' performance on user companies after the issuance of the Job Creation Act. This research uses empirical juridical research methods.From the results of the study that the user company must make a selection on the credibility of the company and the quality of the workforce to be employed as well as an agreement containing articles on supervision between the user company and the outsourced company.Keywords: Juridical Analysis, Managerial Supervision, Outsourcing, Job Creation Act.